Farthest north lake and fjord populations of calanoid copepod Limnocalanus macrurus and Drepanopus bungei in the Canadian high Arctic - Van Hove, P; Kerrie Swadling; Gibson, JAE; Belzile, C; Vincent, WF (2001)
The zooplankton assemblages of Lake A and Disraeli Fjord, northern Ellesmere Island (83Â°N, 75Â°W), were surveyed in early summer 1999. In permanently ice-covered Lake A, two glacial relict calanoid copepod species (Drepanopus bungei and Limnocalanus macrurus) were found in the top 30 m. All developmental stages of the more abundant D. bungei were present, whereas only adults of L. macrurus were found. Analysis of gut contents showed that L. macrurus preyed upon the smaller species. A net tow sample of zooplankton from Disraeli Fjord was mainly composed of D. bungei and L. macrurus, along with two marine cyclopoid copepods (Oncaea borealis and Oithona similis). These two zooplankton communities occur within unusual environments that are strongly inftuenced by perennial ice and snow. They will be subject to major habitat disruption should the current warming trends continue in the north polar region.